MAKING A COMPELLING CASE FOR ESG & ISLAMIC FUNDS: AN EMPIRICAL INVESTIGATION IN COMPARISON WITH CONVENTIONAL FUNDS - Abdullah, Aasim; Rao, Ullas (Indian Journal of Finance and Banking, 2022)
The purpose of this research is to analyze and evaluate the performance of ESG funds and Islamic funds vis-à-vis conventional mutual funds, whereby ESG funds and Islamic funds take into account environmental, social, governance and Shariah-based factors into account during portfolio structuring. To conduct this study, the approach primarily employed the publicly available data of thirty funds from each aforementioned category, calculated their logarithmic returns based on closing prices and subsequently ranked the funds according to the returns. Ten of the top-ranking funds were then selected (owing to some limitations of market data availability) for the methodology to calculate performance using descriptive statistics, one-sample t-tests, portfolio performance measures (Sharpe ratio, Treynor ratio, Jensen’s Alpha) and the well renowned Fama-French three-factor model. The results show that much of the excess returns across a majority of the funds (in all categories) are largely explained by the market premium, while the fund manager skill, SMB and HML factors do not lend much weight in explaining the excess returns attributable to the funds. Furthermore, a considerable finding of this study is that ESG and Islamic funds are not underperforming, but exhibit resilience, and has the potential to evolve and become mainstream options for investments. JEL Classification Codes: B26, G11, G15, G23, M14.